FEATURES OF ACTIVATION OF SPEECH ACTIVITY OF STUDENTS OF NATIONAL GROUPS - Norboeva Dilafruz Jumakulovna (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the issues of improving the effectiveness of classroom lessons are considered, taking into account the psychological characteristics of the trainees. The article emphasizes what skills a student should have at the initial stage. Recommendations are also given when at what stage it is possible to conduct games, game studies. It is possible to intensify speech-cogitative activity only when each student is interested in it.